Desain Protokol Keamanan Data Berbasis Blockchain pada Pengolahan Data Pengguna Aplikasi E-commerce - Firdani, Ella; Hanif, Isa Faqihuddin (LPPM Universitas Mulia, 2025)
This study aims to design the user interface (UI) and user experience (UX) of the Golkar Party National Witness Agency (BSNPG) website as a strategic medium in supporting public information disclosure and increasing public understanding of the institutional functions of BSNPG in the context of elections. To achieve this objective, a Design Thinking approach consisting of five stages was used: Empathize, Define, Ideate, Prototype, and Test. User needs were identified through interviews and surveys involving BSNPG members and the general public as potential users. Based on these results, a website prototype was designed and its usability was tested using the System Usability Scale (SUS) method. The evaluation was conducted by distributing questionnaires to 30 respondents, and the results showed an average score of 71.33%. This score falls into the good and acceptable category, indicating that the prototype successfully meets the aspects of comfort, ease of use, and functional effectiveness from the users' perspective. These findings indicate that the BSNPG website design not only enhances public access to information but also strengthens the institutional image of BSNPG as a professional, transparent, and inclusive organization supporting democratic processes. This study also underscores the importance of adopting a user-centered approach in the development of digital systems for political organizations.